2019
DOI: 10.33549/physiolres.934148
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondins Differentially Regulate Proteins Involved in Arterial Remodeling

Abstract: Thrombospondins (TSPs) are matricellular glycoproteins expressed in response to vascular injury. TSP-1 and TSP-2 are promotors of arterial remodeling while TSP-5 is believed to be protective. The current study assessed the differential effect of TSPs on protein expression in vascular smooth muscle cells (VSMCs). We hypothesized that TSP-1, TSP-2 and TSP-5 would regulate VSMC proteins involved in arterial remodeling. Human VSMCs were exposed to TSP-1, -2, -5 or serum free media (24 hours). Cell lysates were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Its spatial structure is relatively stable, and TSP participates in the communication between cells and the intercellular matrix. Its main functions involve early embryonic development, damage repair, and tumorigenesis [ 10 , 11 ]. The molecular weight of TSP2 is approximately 145 kD; it is a trimeric structure sensitive to Ca2+ and maintained by disulphide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Its spatial structure is relatively stable, and TSP participates in the communication between cells and the intercellular matrix. Its main functions involve early embryonic development, damage repair, and tumorigenesis [ 10 , 11 ]. The molecular weight of TSP2 is approximately 145 kD; it is a trimeric structure sensitive to Ca2+ and maintained by disulphide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, histological examination of aortic wall remodeling by nicotine by Rodella et al [133] indicated a significant upregulation of thrombospondin-1 (TSP-1), TGF-β1, plasminogen activator inhibitor-1 (PAI-1), and CD31 levels in VSMCs in the media in response to 100 µg/mL nicotine in drinking water. TSP-1 is a glycoprotein secreted by VSMCs in response to injury that mediates VSMC proliferation and migration [134] and arterial remodeling [135]. PAI-1, on the other hand, promotes the migration of VSMC by binding to the low-density lipoprotein receptor-related protein (LRP) [136].…”
Section: Nicotine In Vsmc Biology and Phenotypic Switchmentioning
confidence: 99%
“…Its spatial structure is relatively stable, and it participates in the communication between cells and the intercellular matrix. Its main functions involve early embryonic development, damage repair, and tumorigenesis [10,11]. The molecular weight of TSP2 is about 145kD; it is a trimeric structure sensitive to Ca2 + and maintained by disul de bonds.…”
Section: Introductionmentioning
confidence: 99%